Implementation of the Science Technology Engineering Art and Mathematics (STEAM) Approach With the Assistance of Canva Media to Increase the Scientific Literacy of Primary School Students - Rinanda Aprillionita; Fitri Nuraeni; Afridha Laily Alindra (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The scientific literacy of Indonesian elementary school students is one of the lowest in the world. As was found in fifth-grade of the Subang Regency Elementary School, it was found that there was a lack of scientific literacy skills, especially in science process skills. This is caused by the lack of teachers in directing their students to relate science to the environment and technology. Based on this, this research was conducted to analyze students' learning activities and scientific literacy by applying the STEAM approach assisted by Canva media. The method applies the Kemmis & McTaggart Model Classroom Action Research (CAR) design (quantitative & qualitative). The data collection techniques used were observation, tests, and documentation by making 28 fifth-grade students of one of the elementary schools in Subang Regency (14 boys and 14 girls) the research subjects. This research was conducted for ten days from 27 May – 07 July 2024. This research found increased student activity and learning outcomes after implementing the STEAM approach assisted by Canva media. The results of student learning activities increased by 13%, from cycle 76%, to 89% in cycle II. Meanwhile, the results of students' scientific literacy ability tests also increased by looking at the comparison of classics completion from pre-cycle and cycle II of 72% from the pre-cycle test of 14%, the second cycle test being 86%. It can be concluded that the application of the STEAM approach assisted by Canva media can improve the learning activities and scientific literacy abilities of fifth-grade elementary school students in IPAS learning. Future researchers should research further regarding the third scientific literacy skill competency indicator